Trends in contact lens microbial keratitis 1999 to 2015: a retrospective clinical review. (1st May 2019) - Green, Matthew; Sara, Sergio; Hughes, Ian; Apel, Andrew; Stapleton, Fiona
Abstract: Importance: Contact lens microbial keratitis (CLMK) is the most common cause of microbial keratitis in our community. Background: Define the trend in rate of CLMK and define patient demographics/culture results that may have a predictive value in patients with CLMK. Design: Retrospective review of clinical records of patients with MK. Participants: All patients with positive corneal scraping between 1999 and 2015 at the Princess Alexandra Hospital, Brisbane, Queensland identified through local microbiology database. Methods: Trend in CLMK tested with chi‐squared test of peak 3 years vs other years and Poisson regression of interrupted time series. Patient characteristics predictive of CLMK were defined by creating a polynomial regression model by stepwise variable selection. Main Outcome Measures: Yearly rate of CLMK. Results: Records of 895 episodes of MK were included. The most common: risk factor was contact lens wear (324, 36.2%), isolated organism was Pseudomonas aeruginosa ( P. aeruginosa 181, 55.9%) and treatment was monotherapy with a fluoroquinolone 172, 53%). CLMK was most common between 2009 and 2011 (49.5% vs other years 32%, P < 0.001). Poisson regression of the interrupted time series showed there was a significant decrease in the rate over time after 2010 ( P < 0.001). Independent factors predictive of CLMK in multivariate regression were young age (15‐49 years) and corneal culture positive for P. aeruginosa Conclusions and Relevance: The rate of CLMK in our community ranged between 32% and 50% and the rate of disease appears to have peaked during 2009 to 2011 and subsequently declined.